Traction-based multi-scale nonlinear dynamic modeling of bolted joints: Formulation, application, and trends in micro-scale interface evolution. (May 2020) - Balaji, Nidish Narayanaa; Chen, Wei; Brake, Matthew R.W.
Highlights: A multi-scale modeling framework bridging micro-surface features and macro-dynamics. A coupled modal quasi-static solver employed for the dynamic characterization. Rough contact models used for constitutive modeling with Zero-thickness elements. Effectiveness of the framework demonstrated through validation with experimental data. Abstract: A new framework for modeling the dynamics of bolted structures is proposed that considers the nonlinear interfacial modeling of bolted structures using multi-scale traction-based contact constitutive laws implemented through Zero-Thickness Elements (ZTE). Using rough contact theory, it is possible to establish fundamental constitutive relationships with parameters estimated from micro-scale surface scans. Such a model is employed in the framework for a three bolt lap-joint benchmark (the so-called "Brake-Reuß-Beam"). Since the characterization of the interface is conducted in a full-field manner on top of a finite element mesh, the framework is also demonstrated to be applicable for conducting full-field micro-scale interface evolution studies. Preliminary studies are conducted to establish correlations of local changes in relevant roughness parameters with predicted local tractions and dissipation fluxes.